From Empowerment to Prehension: An Analysis of Social Programs from Actor-Newtork Theory [del Empoderamiento a la Prehensión: Un Análisis de Programas Sociales Desde la Teoría del Actor-Red] - Winkler-Muller, M; Castillo-Sepulveda, J (Universitat Autonoma de Barcelona, 2019)
Empowerment has been promoted by government programs as a strategic enclave of social development. In conventional terms, it is understood as a process of taking power, promoting autonomy and responsibility in the face of socio-cultural conditions. In this paper, we propose a variation of that perspective using actornetwork theory as an analytical perspective. From the description of the relationships between practices and technical entities exposed by designers, professionals and users of three social programs in Chile, we expose how these can be understood as heterogeneous assemblages in which are articulated new capacities for involved agents. In that sense, instead of being an eminently social process, we expose empowerment as the emerging agency in socio-technical mediation processes. At last, according to the concept proposed by A. N. Whitehead, we indicate how such a process formulated in human and non-human relations can be understood as prehension. © 2019 Universitat Autonoma de Barcelona.